2018
DOI: 10.1021/acs.jafc.8b01871
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Crops’ Compositional Characteristics: What Do Experimental Data Show?

Abstract: Common pillar across the risk assessment strategies implemented worldwide for genetically modified plants is the comparison of their compositional profile to that of conventional counterparts deemed safe. If differences are observed, those that cannot be attributed to natural variation are further evaluated for their safety relevance. This principle is clear, but its implementation is challenging. Here we first discuss the difficulties of estimating natural variation of crop-specific compositional end-points a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Such high noise levels appear to be inherent in the EFSA equivalence approach and are most likely attributable to (1) the limited genetic diversity for the reference lines, (2) differences in the variability across and within growing environments from study to study, (3) how the composition of the reference lines compares with the compositional diversity of the crop as a whole, and (4) how the genetics of the reference lines compares with the background genetics of the GE variety (non-GE genetics of the isoline) . Perhaps for this reason, some EFSA scientists are beginning to advocate for the use of a non-GE-crop-composition database similar to the one hosted by ILSI, which is used by regulators in other parts of the world to establish reference intervals . It is noteworthy that the majority of the data contained in the ILSI crop-composition database originated from regulatory studies that included non-GE reference lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such high noise levels appear to be inherent in the EFSA equivalence approach and are most likely attributable to (1) the limited genetic diversity for the reference lines, (2) differences in the variability across and within growing environments from study to study, (3) how the composition of the reference lines compares with the compositional diversity of the crop as a whole, and (4) how the genetics of the reference lines compares with the background genetics of the GE variety (non-GE genetics of the isoline) . Perhaps for this reason, some EFSA scientists are beginning to advocate for the use of a non-GE-crop-composition database similar to the one hosted by ILSI, which is used by regulators in other parts of the world to establish reference intervals . It is noteworthy that the majority of the data contained in the ILSI crop-composition database originated from regulatory studies that included non-GE reference lines.…”
Section: Discussionmentioning
confidence: 99%
“…22 It has been suggested that the range of analyte values from a sample of varieties and growing environments, such as those included in the ILSI crop-composition database, is too wide to protect against the risk associated with adversely altering crop composition. 21 However, extreme composition values within a Figure 1. Across-study comparison of non-GE Maverick soybean equivalence to non-GE soybean reference lines for two amino acids and one fatty acid illustrating disparate equivalency conclusions.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%
“… 10–15 Recently, the empirical distribution curves of compositional end-points for maize and soybean were determined, providing novel information on end-point specific variability relevant to risk assessment. 16 …”
Section: Introductionmentioning
confidence: 99%
“… 14 , 15 Recently, Liu et al showed that unintended changes of Bt rice do not go beyond conventional cross-breeding using the approaches of transcriptomics and metabolomics. 16 …”
Section: Introductionmentioning
confidence: 99%
“…With regard to the difficulty to obtain sufficient reference data in any single study, the use of databases was proposed in several publications. 13,14 However, it should be evaluated if these databases are sufficiently representing the design of the experiments and allow for distinguishing genotypic from environmental variation. With regard to the multiplicity problem, it is currently being discussed whether univariate or multivariate methods are most suitable 1519 and whether the false discovery rate (FDR) is apt or inapt to control false non-discoveries.…”
mentioning
confidence: 99%